Estrous cycle and stress: influence of progesterone on the female brain - Lovick,T.A. (2012)
The female brain operates in a constantly changing chemical milieu caused by cyclical changes in gonadal hormones during the estrous cycle (menstrual cycle in women). Such hormones are highly lipophilic and pass readily from the plasma to the brain where they can influence neuronal function. It is becoming clear that the rapid reduction in peripheral circulating progesterone, which occurs during the late diestrous phase of the cycle, can trigger a withdrawal-like response, in which changes in GABA A receptor expression render hyper-responsive certain brain areas involved in processing responses to stressful stimuli. The periaqueductal gray matter (PAG) is recognised as an important region for integrating anxiety/defence responses. Withdrawal from progesterone, via actions of its neuroactive metabolite allopregnanolone, triggers up-regulation of extrasynaptic GABA A receptors on GABAergic neurons in the PAG. As a consequence, ongoing GABAergic tone on the output cells decreases, leading to an increase in functional excitability of the circuitry and enhanced responsiveness to stressful stimuli during the late diestrous phase. These changes during late diestrus could be prevented by short-term neurosteroid administration, timed to produce a more gradual fall in the peripheral concentration of allopregnanolone than the rapid decrease that occurs naturally, thus removing the trigger for the central withdrawal response.